PASSENGER CAR UNITS FOR DIFFERENT MIDBLOCK SECTIONS IN SRI LANKA UNDER MIXED TRAFFIC CONDITION - Dhananjaya, Dineth; Fernando, Madushan; Silva , Mavin; Sivakumar, Thillaiampalam (Journal of Applied Engineering Science, 2023)
Traffic-related analyses are essential to implementing traffic management approaches to create mobility more convenient. In this context, Passenger Car Unit (PCU) values as a uniform measure of vehicles are instrumental in analysis such as traffic capacity estimation, traffic flow model development, level of service determination, etc. These studies always demand a recently calculated set of PCU values since the traffic conditions in arterials often change. PCU values for expressway and three-lane (one-way) road types have not been calculated in the Sri Lankan context, and the available set of values has become somewhat outdated. Hence, this study used Chandra's method to assess the PCU values of ten vehicle categories for four different mid-block road sections in the Colombo district, Sri Lanka. The data relating to the two main variables of this method, categorical speed, and area of vehicles, were collected from field surveys. The results of four-lane arterials were aggregated and compared with the existing PCU values, intending to propose an updated set for general transportation studies in Sri Lanka.
Keywords: Passenger Car Unit (PCU), heterogeneous traffic, mixed traffic, midblock road sections, chandra's method